Faktor Perawat terhadap Kejadian Medication Administration Error di Instalasi Rawat Inap - Vidia Sabrina Budihardjo (Universitas Airlangga, 2017)
Medication administration error is one of medication error that happened due to unfulfillment of drug instruction or drug administration that is different with the recipe. From the initial survey conducted in 2015, there were 13 events medication errors known in 2014-2015 in RSU Haji Surabaya. Based on Kepmenkes RI nomor 129/Menkes/SK/II/2008 about Minimum Service Standards, medication incident should not be any error occurred in the Hospital.This study was an observational descriptive study aimed to identify factors that contribute to the incidence of medication errors. Respondents were 56 nurses that worked on 7 inpatient wards. Variablesi n this research are: the skills of nurses, nurse's knowledge, and communication between nurse and patients. The result showed that the incidence of medication error in 2014-2016 amounted to 14 events that occurred in most of the inpatient ward (57.1%). Most of inpatient ward (57.41%) had good skill of nurses, most of the inpatient wards (57.1%) had a sufficient knowledge and communication of nurses.From this study it can be concluded that the skills of nurses, nurse's knowledge, communication between nurse and patients are contributing to the incidence of medication errors in RSU Haji Surabaya. Keywords: inpatient ward, medication errors, nurses